Baculovirus and Plasmid Vector-Mediated Gene Transfer in Daphnia magna Cells in Primary Embryonic In Vitro Cultures in an Optimized Microenvironment: Methods and Protocols - C. Sreevidya; Soumya Balakrishnan; Jayesh Puthumana (Bio-Protocol)
Daphnia magna is a well-established model organism in ecotoxicology, environmental monitoring, and genetics due to its sensitivity to pollutants, its pivotal role in freshwater ecosystems, and its well-characterized genome. Despite its extensive use in these fields, there is a notable lack of established protocols for developing primary cell culture systems and conducting transgenic studies in Daphnia spp. This study addresses these gaps by optimizing a medium and standardizing protocols for primary cell culture and transgenic experiments in D. magna. Primary cell cultures were established from both D. magna embryos and whole organisms, with medium optimization verified using XTT assay. Cell viability was sustained for over two months using a modified Schneider’s insect medium enriched with FBS, glucose, MEM vitamin mix, and selenium. DNA replication and cell proliferation were confirmed through BrdU labeling. Both mechanical and enzymatic passaging methods were compared, resulting in 20% and 10% cell attachment, respectively. For transgenic applications, this study successfully standardized plasmid-mediated lipofection and baculovirus-mediated transduction, achieving success rates of 52% and 45%. These findings represent a pioneering effort in D. magna embryonic cell culture, offering a reliable in vitro platform for future biological research, including ecotoxicological and epigenetic investigations. The established protocols and optimized cell culture medium have significant implications for advancing crustacean cell line research and transgenic model development, enhancing our understanding of biological processes in controlled laboratory environments.